Kewenangan Ombudsman RI pada Aspek Pelayanan Publik - Ariani Zega (Jurnal Hukum Lex Generalis, 2025)
The Ombudsman of the Republic of Indonesia (ORI) is an independent state institution that plays a crucial role in overseeing the implementation of public services, particularly in addressing maladministration practices. This study aims to analyze the Ombudsman's authority under statutory regulations, the implementation of this authority in resolving public service disputes, and strategies to improve its performance effectiveness. The method used is normative legal research with a statutory approach. The results indicate that the Ombudsman's authority is non-judicial but possesses significant moral force, with operational mechanisms that include inspection, mediation, and recommendations. The implementation of this authority still faces challenges such as limited resources and low levels of agency compliance with recommendations. To increase effectiveness, institutional strengthening, political support, public literacy, and the application of ombudsprudence principles as a consistent resolution mechanism are needed. This study confirms that the Ombudsman has significant potential as a catalyst for bureaucratic reform and strengthening the principles of the rule of law in Indonesia.